Community health workers: A crucial role in newborn health care and survival - Samira Aboubaker; Shamim Qazi; Cathy Wolfheim; Adebowale Oyegoke; Rajiv Bahl (Edinburgh University Global Health Society, 2014)
There is ample evidence from research and implementation to show that community health workers, when appropriately trained, supplied, supported and supervised, can identify and correctly treat most children for pneumonia, diarrhoea and malaria. Community management of childhood illness is an important contribution to the remarkable progress in reducing child mortality. Globally, the rate of under-five mortality has decreased by nearly half, from 90 deaths per 1000 live births in 1990 to 46 in 2013.